Particulate Phosphorus in the Everglades Agricultural Area: II-- Transport Mechanisms - Samira H. Daroub; James D. Stuck; Timothy A. Lang; Orlando A. Diaz (EDIS)
This document is SL 198, one of a series of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published November 2002.